METTL16 emerges as a pivotal epitranscriptomic regulator, linking RNA modification, tumor progression, and immune modulation - Wang, Qiang; Jiang, Xiulin; Yuan, Yixiao; Li, Chunhong (Frontiers in Immunology, 2025)
N6-methyladenosine (m6A) modification has emerged as a critical epigenetic mechanism regulating gene expression in diverse physiological and pathological processes, including cancer. Methyltransferase-like 16 (METTL16), a recently identified m6A methyltransferase, has been shown to influence tumor progression through m6A-dependent regulation of key target genes. Accumulating evidence indicates that METTL16 exerts tumor-suppressive or tumor-promoting roles in a context-dependent manner, affecting cell proliferation, apoptosis, autophagy, and chemotherapeutic response across multiple cancer types such as bladder cancer, lung cancer, colorectal cancer, and acute myeloid leukemia. Mechanistically, METTL16 modifies the mRNA stability and translation of oncogenes or tumor suppressors via recognition of m6A sites, and its expression can be regulated by upstream factors including transcription factors and hypoxia-inducible signals. Recent evidence suggests that METTL16 also modulates the tumor microenvironment (TME), potentially affecting immune cell infiltration, immune checkpoint expression, and tumor immune evasion. Collectively, METTL16 emerges as a pivotal epitranscriptomic regulator linking RNA modification, tumor progression, and immune modulation, offering new avenues for precision oncology.